2014
DOI: 10.1111/josh.12177
|View full text |Cite
|
Sign up to set email alerts
|

Positive School Climate Is Associated With Lower Body Mass Index Percentile Among Urban Preadolescents

Abstract: BACKGROUND Schools are an important environmental context in children’s lives and are part of the complex web of factors that contribute to childhood obesity. Increasingly, attention has been placed on the importance of school climate (connectedness, academic standards, engagement, and student autonomy) as 1 domain of school environment beyond health policies and education that may have implications for student health outcomes. The purpose of this study is to examine the association of school climate with body… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…Our findings among females are consistent with findings from Gilstad-Hayden et al (1999), who found a positive relationship between school climate (e.g., My school offers a wide variety of activities to keep students at my school engaged; I feel welcome at my school) and BMI percentile among K–8 students in an urban school district. Our study builds on the study by Gilstad-Hayden and colleagues by exploring personal stress as a mechanism by which school climate is related to weight status.…”
Section: | Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our findings among females are consistent with findings from Gilstad-Hayden et al (1999), who found a positive relationship between school climate (e.g., My school offers a wide variety of activities to keep students at my school engaged; I feel welcome at my school) and BMI percentile among K–8 students in an urban school district. Our study builds on the study by Gilstad-Hayden and colleagues by exploring personal stress as a mechanism by which school climate is related to weight status.…”
Section: | Discussionsupporting
confidence: 91%
“…The indirect effects observed provide some evidence of mediation; however, future studies should examine the relationship between school climate, personal stress, and being overweight over time. The cross‐sectional study design also limits our ability to determine the direction of the relationship between being overweight and school‐stressors; students who are overweight may be bullied (Lumeng et al., ; Mamun, O'Callaghan, Williams, & Najman, ) more often and feel less connected (Puhl, ) to the school (Gilstad‐Hayden et al, ). While this current investigation used a large sample in multiple school districts, generalizability may be a concern since the schools were from a single state.…”
Section: Discussionmentioning
confidence: 99%
“…The school environment plays an important role in children's cognitive development and educational outcomes. School climate has been identified as a powerful multidimensional construct associated with children's mental and physical health (Cohen et al., ; Denny et al., ; Gilstad‐Hayden et al., ; LaRusso et al., ; Maxwell, Reynolds, Lee, Subasic, & Bromhead, ; Shochet et al., ; Thapa et al., ; Wang, ; Way et al., ) and academic achievement (Bond et al., ; Brand et al., ; Wang & Holcombe, ). The goals of this study were to examine associations of school climate with children's cortical structure (cortical thickness and surface area) and EF, and to explore the role of school climate as a mediator or moderator of socioeconomic differences in cortical structure and EF.…”
Section: Discussionmentioning
confidence: 99%
“…A supportive school climate has been positively associated with mental and physical health (Cohen, McCabe, Michelli, & Pickeral, ; Denny et al., ; Gilstad‐Hayden et al., ; LaRusso, Romer, & Selman, ; Shochet, Dadds, Ham, & Montague, ; Wang, ; Way, Reddy, & Rhodes, ) and academic achievement (Bond et al., ; Brand, Felner, Seitsinger, Burns, & Bolton, ; Sherblom, Marshall, & Sherblom, ; Wang & Holcombe, ), and has been associated with reduced rates of risky sexual behavior, violence, and drug use (Catalano, Oesterle, Fleming, & Hawkins, ; LaRusso et al., ; Wang, Selman, Dishion, & Stormshak, ). These findings raise questions about the ways in which school climate may be associated with more specific underlying neurocognitive skills as well as the developing brain.…”
Section: Introductionmentioning
confidence: 99%
“…Future studies are needed to identify additional aspects of the school context and environment that may contribute to the risk of obesity throughout the life course. For example, “school climate (eg, feeling close to people at school or perceiving that teachers treat students fairly)” has been longitudinally associated with other health behaviours, such as substance use and associated with BMI percentiles in a smaller cross‐sectional study . Since school plays an important role in children's and adolescents' developing attitudes and values related to health, it would be worth exploring whether such factors have a long‐term association with obesity and can be promoted through interventions.…”
Section: Discussionmentioning
confidence: 99%